Drug abuse in the practice of the endocrinologist - I. V. Madyanov; A. V. Golenkov (Лечащий Врач, 2021)
The article summarizes the cases of endocrine drug abuse by patients. 57700 calls for outpatient admission to endocrinologists and admission to endocrinological hospitals were analyzed. It is concluded that it is difficult to manage endocrinological patients who abuse drugs. Solution of this problem requires joint efforts of endocrinologists, drug treatment specialists, psychiatrists and psychologists.